Pengaruh Stres Kerja Dan Work-life Balance Terhadap Kinerja Karyawan Pada Industri Konveksi Nano Sportwear: The Effect of Work Stress and Work-Life Balance on Employee Performance in the Nano Sportwear Garment Industry - Arneta Mutiara Putri Sumarna; Murniyati Murniyati (CV Warnak Johanna Nusantara, 2026)
Insufficient work stress can lower productivity, while work-life balance helps maintain employee performance. At Nano Sportwear, high workloads often trigger stress and reduce performance. This study aims to analyze the effect of work stress and work-life balance on employee performance. The research employed a quantitative statistical approach using a questionnaire method. Saturated sampling was applied, involving the entire population of 35 employees. Data were collected through structured questionnaires distributed via Google Forms and analyzed using the T-test for partial effects and the F-test for simultaneous effects. The results indicate that work stress significantly affects employee performance T value 5.898 and sig 0.000. Work-life balance also has a significant influence T value 2.117 and sig 0.042. Simultaneously, both variables impact performance with an F-value of 157.515 and sig 0.000. These findings confirm that effective stress management and the creation of work-life balance are essential for enhancing employee performance in Nano Sportwear’s garment industry